PPARβ/δ-dependent MSC metabolism determines their immunoregulatory properties - Contreras-Lopez, R. A.; Elizondo-Vega, R.; Torres, M. J.; Vega-Letter, A. M.; Luque-Campos, N.; Paredes-Martinez, M. J.; Pradenas, C.; Tejedor, G.; Oyarce, K.; Salgado, M.; Jorgensen, C.; Khoury, M.; et al. (Scientific Reports, 2020)
Mesenchymal stem cell (MSC)-based therapy is being increasingly considered a powerful opportunity for several disorders based on MSC immunoregulatory properties. Nonetheless, MSC are versatile and plastic cells that require an efficient control of their features and functions for their optimal use in clinic. Recently, we have shown that PPARβ/δ is pivotal for MSC immunoregulatory and therapeutic functions. However, the role of PPARβ/δ on MSC metabolic activity and the relevance of PPARβ/δ metabolic control on MSC immunosuppressive properties have never been addressed. Here, we demonstrate that PPARβ/δ deficiency forces MSC metabolic adaptation increasing their glycolytic activity required for their immunoregulatory functions on Th1 and Th17 cells. Additionally, we show that the inhibition of the mitochondrial production of ATP in MSC expressing PPARβ/δ, promotes their metabolic switch towards aerobic glycolysis to stably enhance their immunosuppressive capacities significantly. Altogether, these data demonstrate that PPARβ/δ governs the immunoregulatory potential of MSC by dictating their metabolic reprogramming and pave the way for enhancing MSC immunoregulatory properties and counteracting their versatility.
CRIS-Team Scopus Importer:2020-07-24